Your daughters do not give to their sons and their daughters do not take for your sons (Ezra 9,12) intermarriage in Ezra 9-10 and in the pre-Maccabean Dead Sea Scrolls ; Teil 2 - Lange, Armin 1961- (2008)
Ancient Jewish literature in general and the pre-Maccabean literature from the Qumran library in particular allow for a better understanding of Ezra’s marriage reforms and their interpretation by the final stage of the book of Ezra / Nehemiah. Ezra’s measure of enforced mass divorce is unique in Second Temple Judaism which argues for its historicity. Ezra’s marriage reforms were probably motivated by a democratization of priestly intermarriage prohibitions. In light of the (enforced) Hellenistic acculturation of Ptolemaic Yehud, the final redaction of the book of Ezra Nehemiah reads Ezra’s marriage reform as a fight for the preservation of the religious and cultural identity of Judaism.
Die antik-jüdische Literatur und besonders die vormakkabäischen Texte aus der Bibliothek von Qumran werfen neues Licht auf die Frage nach Esras Umgang mit Mischehen einerseits und auf die Interpretation von Esras Maßnahmen in der Schlussredaktion des Esra-Nehemia-Buches andererseits. Die erzwungene Massenscheidung von Mischehen unter Esra ist singulär in der Geschichte des Judentums aus der Zeit des Zweiten Tempels. Diese Einmaligkeit spricht für die Historizität der Maßnahme. Im Kontext anderer perserzeitlicher jüdischer Literatur scheint es wahrscheinlich, dass Esras Einstellung zur Mischehenfrage von einer Demokratisierung priesterlicher Vorschriften und Ideen geprägt ist. Die Schlussredaktion des Esra-Nehemia-Buches interpretiert Esras Umgang mit Mischehen im Licht der zunehmenden Hellenisierung der ptolemäischen Provinz Jehud und versteht Esras Maßnahmen als einen Kampf um die Bewahrung der kulturellen und religiösen Identität des Judentums.
Keywords: Bibel; Dead Sea Scrolls; Mischehe